Incorporating A Learner Development Programme into A Self-access Centre in A University in Southern Taiwan - Huang, Hui-Fen (2010)
It has been pointed out that Taiwanese university students tend to be teacher dependent and not given enough opportunity to make decisions on their own learning when it comes to learning a foreign language (Chu, 2007; Cheng, 2006; Cheng, 2007; Cheng, 2008; Lin, 2009). Moreover, although more and more Taiwanese universities have established self-access centres, the facility is not widely used by students (Cheng 2008; Cheng 2007). This paper, therefore, proposes that integrating a learner development programme into a self-access centre in a Taiwanese university can be a solution to the issues mentioned above.